Individual Differences in Sequential Movement Coordination in Hip-Hop Dance: Capturing Joint Articulation in Practicing the Wave - Brown, Derrick D.; Wijffels, Guido; Meulenbroek, Ruud G. J. (Frontiers in Psychology, 2021)
The current study highlights individual differences in the joint articulation strategies used by novices practising a hip-hop dance movement, the wave. Twelve young adults, all naive regarding hip-hop dance performance, practised the wave in 120 trials separated into four blocks with the order of internal or external attentional focus counterbalanced across subjects. Various kinematic analyses were analysed to capture performance success while exploiting the observed individual differences in order to establish the reliability of the proposed performance indicators. An external focus of attention marginally facilitated the smooth transfer of a wave motion across neighbouring limb segments as characterized by a constant propagation speed combined with large wave amplitudes. Systematic correlations between the success indicators were found, exemplifying the various degrees of joint articulation that novices prove capable of during an initial practising session to try and perform a novel complex motor task.